Evolusi Manajemen Keuangan Digital dan Inklusi Keuangan di Indonesia: Kajian Sistematis melalui Analisis Bibliometrik dan Sintesis Tematik - Muhammad Haris Saputra; Kurnia Permana (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the development and challenges of digital finance in supporting financial inclusion in Indonesia through a systematic review of relevant literature. This study used the Systematic Literature Review method with PRISMA guidelines, combined with bibliometric analysis to map publication trends and thematic analysis to identify conceptual patterns within the five main pillars of digital finance. The analysis process was conducted iteratively with validation between researchers to ensure consistency of results. The results indicate that digital finance plays a significant role in expanding access to financial services, increasing transaction efficiency, and national economic growth. However, challenges remain, including infrastructure inequality, data security, and financial literacy gaps in rural areas. This study contributes to the development of financial management science by emphasizing the importance of collaboration between regulators, industry, and the community in creating an inclusive, ethical, and sustainable digital financial ecosystem.